Millikelvin Intracellular Nanothermometry with Nanodiamonds - Sow, Maabur; Mohnani, Jacky; Genov, Genko; Klevesath, Raphael; Mayerhoefer, Elisabeth; Mindarava, Yuliya; Blinder, Rémi; Mandal, Soumen; Clivaz, Fabien; Gonzalez, Raúl B.; Tews, Daniel; Laube, Christian; et al. (Advanced science, 2025)
Nanothermometry within living cells is an important endeavor in physics, as the mechanisms of heat diffusion in such complex and dynamic environments remain poorly understood. In biology, nanothermometry may offer new insights into cellular biology and open new avenues for drug‐discovery. Previous studies using various nanothermometers have reported temperature variations of up to several Kelvins during metabolic stimulation, but these findings have remained controversial as they appear to contradict the law of heat diffusion in the presence of heating rates that are consistent with physiological parameters. Here, nanodiamond nanothermometry are reported inside macrophages by measuring the optically detected magnetic resonance spectra of nitrogen‐vacancy centers. The spectra are analyzed when cells are metabolically stimulated and after cell death. It is shown that, in the experimental setting, the apparent spin resonant spectral shifts can be misinterpreted as temperature changes but are actually caused by electrical field changes on the nanodiamond's surface. These artifacts are addressed with optimized nanodiamonds and a more robust sensing protocol to measure temperature inside cells with precision down to 100 mK (52 mK outside cells). No significant temperature changes upon metabolic stimulation are found, a finding consistent with the implementation of the heat diffusion law and expected physiological heating rates.